Analisis Kelayakan Finansial Agroindustri Kerupuk Amplang Udang di Kecamatan Tembilahan Kabupaten Indragiri Hilir (Studi Kasus Pada Agroidustri Kerupuk Amplang Udang Jumelda) - Dessy Adrika; Yusmini '; Juin’atri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purposes of this research are to acknowledge the financial feasibility of the agro-industry amplang prawn crackers Jumelda (in NPVJRR, Net B’C) and to see the le1el of ssitivitv on afro-industries.. if there is a change in the level of prices of raw materials (shrimp and tapioca flour) and a decreasing in production scale. Based on the analysis of investment criteria which carried on the business life of 20-year period, obtained the NPV ‘s value is Rp .676. 205.478,31, the IRR’ s value is higher than discount rate: that is 44:66%, and Net B.’C’s value is 329. The results of the sensitivity analysis on 20% of the shrimp raw price increasing obtained Rp.611.770.3897:42 of NPV’s value with percentage change of NPV’s value is 9,53%.. The sensitivity analysis of 17% increasing on tapioca flours price resulting Rp.650.983.013:94 of NPV’s value with perc.itage change in NPV is 3,73%. The results of the sensitivity analysis when the reduction in the scale of production is more than 35,41% thai the agro-industry is no longer feasible to run and delop, because on that condition the value of NPV is already negative, net value of B I C is less than one and the IRR’ s value is less than the cost of capital which has been detecmined at 1 8% (IRR <DR) Keywords: agroindustry, finacial analysis, sensitivity analysis